Analysis of time management and self-management work practice by leaders – a focus group study - Gyopár Csapai, Erzsébet; Varga, Dorottya; Berke, Szilárd (Applied Studies in Agribusiness and Commerce, 2020)
Nowadays excellent leadership is one of the foundations of high organizational performance. Leadership excellence is a complex topic but efficiency and effectiveness are important components of it. These are closely linked to self-management and time management. In our focus group research, we asked senior executives about how they organize their average workday. We used two theoretical models: the Blue Ocean model and the Franklin Covey time-matrix. According to the participants the key component of effective self-management is the time management. In their leadership practice they often use a digital task manager, a workshop, an informal meeting as a tool and they find knowledge sharing also very important. They try to approach their employees empathetically. They would like to reduce the administrative tasks, spend less time on correspondence, travel and “small talks”. They would like to spend more time on automation and communication, further training and team work and dealing with the employees. They think that strategic planning, market analysis, sales, knowledge development and transfer should require more planning.JEL code: M12